2011
DOI: 10.1080/10640266.2011.551629
|View full text |Cite
|
Sign up to set email alerts
|

Treatment Results of Anorexia Nervosa and Bulimia Nervosa in a Residential Treatment Program

Abstract: Data on the effectiveness of residential treatment for patients with anorexia nervosa (AN) and bulimia nervosa (BN) are limited. We analyzed patient survey results at admission and discharge from Monte Nido Residential Treatment Program. Of 287 consecutive admissions, 80% (231) "graduated" (completed ≥ 30 days of treatment), and of these (all of whom gave consent), only patients with AN (N = 120) or BN (N = 95) were included (215 of 231, 93%) in this study. Analyses included a comparison of admission vs. disch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 14 publications
0
26
1
Order By: Relevance
“…The residential treatment programmes discussed in this review (Brewerton & Costin, , Delinsky et al, ; Hoffart, Lysebo, Sommerfeldt, & Rø, ; Lowe et al, ; McHugh, ; Weltzin et al, ) are 24‐hour care facilities designed specifically for patients with ED that do not require continuous medical monitoring, all of which primarily used CBT and/or dialectical behaviour therapy in addition to other treatment modalities (e.g. interpersonal, psychodynamic, art therapy).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The residential treatment programmes discussed in this review (Brewerton & Costin, , Delinsky et al, ; Hoffart, Lysebo, Sommerfeldt, & Rø, ; Lowe et al, ; McHugh, ; Weltzin et al, ) are 24‐hour care facilities designed specifically for patients with ED that do not require continuous medical monitoring, all of which primarily used CBT and/or dialectical behaviour therapy in addition to other treatment modalities (e.g. interpersonal, psychodynamic, art therapy).…”
Section: Resultsmentioning
confidence: 99%
“…Two residential treatment studies included an adult‐only sample, and both revealed improvements across most outcome measures (Brewerton & Costin, , , Hoffart et al, ) (Table ). One of the studies evaluated patients with BN and reported a significant reduction in binge frequency, without a reduction in purge frequency, although specific scores were not provided, making the finding difficult to interpret (Hoffart et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…Half of deaths were due to suicide, while other causes included alcohol abuse or medical consequences of marasmic malnutrition [5]. Short-term evaluations showed good outcomes ranging from 18 [6] to 42 % [7]. The 4-year or 5-year clinical recovery rate was higher and it was influenced by the duration of follow-up [8][9][10][11].…”
Section: Introductionmentioning
confidence: 90%
“…Residential treatment programmes have been found to be effective in the treatment of AN and BN both post-treatment and at 3–4 year follow-up [101,102]. Treatment for EDs may also take place within substance abuse treatment programmes, however not all such programmes are equipped with adequate knowledge or resources [93].…”
Section: Reviewmentioning
confidence: 99%